Effect of subacute poisoning with selected pyrethroids on fresh spatial memory and movement activity in mice - Konopelko, Michał; Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2020)
Introduction. Pyrethroids are commonly used in agriculture and for indoor insect control. They act as neurotoxins mainly via sodium channels in neurons. People can be exposed to traces of these xenobiotics dermally, with food, at home or at workplace. Three pyrethroids: cypermethrin, lambdacyhalothrin, and betacyfluthrin were chosen for modelling subacute oral poisoning in mice. The aim of the study was to assess if 7-day exposure to 0.1LD50 of each compound could impair memory and motor activity in mice. Material and methods. A total of 64 mice were divided into 8 groups of 8 animals: females controls, males controls, females receiving cypermethrin, males receiving cypermethrin, females receiving lambdacyhalothrin, males receiving lambdacyhalothrin, females receiving betacyfluthrin, males receiving betacyfluthrin. They were given 0.1LD50 of a pyrethroid dissolved in canola oil by gavage daily for 7 days. They were tested in a Y-maze on day 1 and 7. Results. Subacute poisoning with betacyfluthrin significantly reduces locomotor activity in females on day 1 and in both genders on day 7 without effect on fresh spatial memory. Conclusion. Betacyfluthrin is the most harmful of the tested pesticides.